Polyethylene glycol terephthalate as well as preparation method and application thereof
Through the combination of catalysts A and B, a high mechanical performance polyethylene terephthalate was prepared for LED lampshades, which solved the problem of the degradation of polyethylene terephthalate in high temperature environments. The high light transmittance and light diffusion performance of LED lampshades are achieved, meeting the needs of high-performance materials.
Patent Information
- Application Number
- CN202411822929.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyethylene terephthalate has reduced mechanical properties and insufficient heat resistance in high-temperature environments, which limits its use in high-performance materials such as LED lampshades.
Using the combination of catalyst A and catalyst B, polyethylene terephthalate with concentrated molecular weight distribution and excellent mechanical properties is prepared through esterification reaction, pre-polycondensation reaction and final polycondensation reaction, and used to prepare LEDs. Lamp covers to improve its light transmittance and light diffusion properties.
It achieves high mechanical properties and good thermal stability of polyethylene terephthalate, meets the basic requirements of LED lampshades, improves the light transmittance and light diffusion properties of the lampshades, and extends the service life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene terephthalate production, in particular to polyethylene terephthalate and a preparation method and application thereof. Background Art
[0002] Polyethylene terephthalate (PET) is a polymer compound formed by the polycondensation of terephthalic acid and ethylene glycol. PET has good gloss, mechanical properties and chemical resistance. In addition, in a wide temperature range, PET also exhibits good physical and mechanical properties. The long-term use temperature can reach 120°C, and the electrical insulation is excellent. Even at high temperature and high frequency, its electrical properties are still good. At the same time, its creep resistance, fatigue resistance, friction resistance and dimensional stability are all very good.
[0003] Although PET has many advantages, its performance still has some shortcomings in certain specific application scenarios. For example, in terms of strength and heat resistance, the performance of PET may not meet the needs of some engineering plastics applications that require higher strength and heat resistance. Although it has certain strength and heat resistance, compared with some high-performance engineering plastics, its mechanical properties may decline and its optical properties will be affected in high temperature environments or when subjected to large external forces, which limits its application in some fields that require stringent material properties, such as LED lampshades.
[0004] LED lampshade is a product used to protect LED light source and improve its optical performance. It mainly protects light source, improves optical performance and provides safety protection. LED lampshade made of PET has the advantages of good optical performance, excellent mechanical performance and good chemical resistance. It also has good performance in processability and environmental protection. It is also widely used in actual production and life. When LED lamps are in normal use, the temperature of the lamp beads will be high, especially for high-power LED lamp beads. The temperature of the heat dissipation belt can sometimes reach more than 100°C. Existing LED lampshades have problems such as limited heat resistance, insufficient rigidity, and light diffusion performance that needs to be improved. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the object of the present invention is to provide a polyethylene terephthalate having good mechanical properties, such as high tensile strength, bending strength and impact strength, which can meet the basic requirements as a LED lampshade material.
[0006] Another object of the present invention is to provide a method for preparing polyethylene terephthalate, by using catalyst A and catalyst B in combination, the production efficiency of polyethylene terephthalate is greatly improved and the occurrence of side reactions is reduced.
[0007] The third object of the present invention is to provide an application of polyethylene terephthalate for preparing an LED lampshade. The prepared LED lampshade has good light transmittance and light diffusion performance, and can make the light of the LED lamp pass through the lampshade evenly.
[0008] The present invention is achieved by adopting the following technical solutions: The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 225-235°C and a pressure of 0.05-0.3 MPa for 2.5-3.5 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 275-284°C and a pressure of 2550-2800Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 290-295°C and a pressure of 255-285Pa to further grow the molecular chain and obtain polyethylene terephthalate; The catalyst A is a composite catalyst loaded on MCM-41 with p-toluenesulfonic acid and stannous octoate as raw materials, and the catalyst B is a composite catalyst with cerium sulfate and antimony ethylene glycol as raw materials; In the step (1), the mass ratio of ethylene glycol to terephthalic acid is (1.08-1.12):1.
[0009] In the step (1), the amount of catalyst A added is 0.05-0.1% of the total mass of the reactants in the esterification reaction; in the step (2), the amount of ethylene glycol added is 2.2-4% of the mass of ethylene terephthalate oligomers, and the amount of catalyst B added is 0.02-0.04% of the mass of ethylene terephthalate oligomers.
[0010] Catalyst A is made of p-toluenesulfonic acid and stannous octoate and loaded on MCM-41. Its composite catalyst structure can provide more active sites, improve the rate and selectivity of the esterification reaction, and make terephthalic acid and ethylene glycol more efficiently converted into ethylene terephthalate oligomers. Catalyst B is compounded with cerium sulfate and antimony glycol as raw materials. It has good catalytic activity for pre-polycondensation and final polycondensation reactions, and can effectively promote the growth of oligomer molecular chains to obtain high molecular weight polyethylene terephthalate.
[0011] In the step (1), the preparation method of catalyst A comprises the following steps: a. Add the calcined MCM-41 molecular sieve to ethanol and ultrasonically disperse it for 18-25 min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.1-0.5 mol / L, then add the solution dropwise to the suspension of MCM-41, stir at 20-25°C for 8-10h, and stir at a speed of 350-480rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.1-0.2 mol / L solution, add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 12-14h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1, dissolved in toluene to form a mixed solution, added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and stirred at 65-75 ° C for 5-7h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances are detected in the washing liquid, and then dry the filter cake at 95-110°C for 9-10h to obtain a supported composite catalyst, and then calcine the dried catalyst at 385-420°C for 3-6h to obtain catalyst A.
[0012] The loading amount of p-toluenesulfonic acid is 12-16% of the total mass of catalyst A, the loading amount of stannous octoate is 8-10% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 2-4% of the total mass of catalyst A.
[0013] p-Toluenesulfonic acid is a strong organic acid that can donate protons (H +), which protonates the reactant molecules and thus enhances their reactivity. In the esterification reaction, it can make the carbonyl carbon of the carboxylic acid more susceptible to the attack of the alcohol hydroxyl group and promote the formation of ester bonds. The tin atom in stannous octoate has an empty orbital, which can form a coordination bond with the oxygen atom of the alcohol, enhancing the nucleophilicity of the alcohol hydroxyl group, which is also conducive to attacking the carbonyl carbon of the carboxylic acid. When the two are compounded, this synergistic effect can greatly increase the reaction rate, allowing the esterification reaction to proceed under milder conditions and reducing the occurrence of side reactions. The acidic active center of p-toluenesulfonic acid activates the reactants mainly through protonation, while the metal active center of stannous octoate changes the electron cloud distribution of the reactants through coordination, thereby increasing their reactivity. The active centers of the two are complementary, and after compounding, the reactants can be activated from different angles, thereby improving the overall catalytic efficiency of catalyst A. The combination of p-toluenesulfonic acid and stannous octoate can also adjust the selectivity of the reaction; stannous octoate may undergo deactivation reactions such as hydrolysis or oxidation during the reaction, and the presence of p-toluenesulfonic acid can inhibit the occurrence of these deactivation reactions to a certain extent. p-toluenesulfonic acid can react with the moisture in the reaction system to reduce the effect of moisture on stannous octoate, and its acidic environment may also help stabilize the active center of stannous octoate and extend the service life of catalyst A.
[0014] The pores of MCM-41 can adsorb and enrich the reactant molecules. After entering the pores, terephthalic acid and ethylene glycol molecules can be enriched near the acidic active center of p-toluenesulfonic acid, making it easier for carboxyl and hydroxyl groups to react. In addition, the presence of the carrier can limit the aggregation of p-toluenesulfonic acid molecules, so that they exist in the pores in the form of single molecules or small aggregates, thereby maintaining a high catalytic activity. Stannous octoate, as a metal organic compound, can also obtain better dispersion effects after loading. In the esterification reaction of PET, it can form a complex with ethylene glycol to promote the hydroxyl group of ethylene glycol to attack the carboxyl group of terephthalic acid. After loading on MCM-41, this coordination effect is more effective because the dispersion of its active sites is enhanced, which is conducive to coordination with the reactants, thereby increasing the reaction rate. The surface properties of MCM-41 can regulate the activity of stannous octoate. Functional groups such as hydroxyl groups on the surface of the carrier can interact with stannous octoate, change its electron cloud distribution, and make it easier to coordinate with ethylene glycol. At the same time, in the pore environment, the collision frequency between the reactant molecules and stannous octoate increases, allowing the reaction to proceed more efficiently. The phosphorus atom in triphenyl phosphate has a lone pair of electrons, which can interact with the acidic center of p-toluenesulfonic acid and the metal center of stannous octoate. This interaction may be a coordination bond or a weak electrostatic interaction. In this way, it can adjust the chemical environment around the active center of catalyst A to make it more stable. It may also have a certain effect on the adsorption and activation of the reactant molecules, which helps to improve the selectivity of the reaction. The boron atom in boric acid has an empty orbital and can accept the electron pair of the acidic center of p-toluenesulfonic acid to form an acid-base interaction complex. The presence of this complex can change the electron cloud density of the carboxyl group of terephthalic acid, making it more susceptible to attack by the hydroxyl group of ethylene glycol. In addition, there may be a weak coordination effect between boric acid and stannous octoate, which can optimize the coordination mode of stannous octoate and ethylene glycol and improve the reaction efficiency. The cationic part of tetrabutylammonium bromide (tetrabutylammonium ion) can interact with the anionic part of terephthalic acid, transferring terephthalic acid from the organic phase (if present) to the phase where ethylene glycol is located. At the same time, its bromide ion part can form hydrogen bonds or other weak interactions with ethylene glycol, increasing the contact opportunity between the two. This phase transfer effect can enable p-toluenesulfonic acid and stannous octoate to better play a catalytic role because the effective collision frequency between the reactants increases, thereby improving the rate and efficiency of the esterification reaction.
[0015] In the step (2), the preparation method of catalyst B comprises the following steps: ① Calcine the silicon dioxide at 550-600°C for 4-6 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.3-0.8 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 18-28 hours; ② Dry the impregnated sample at 100-120°C for 16-20h, and then calcine at 450-550°C for 3-6h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then drop tetrabutyl titanate into the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 3-6 hours, then add the ethylene glycol antimony solution to the above system, and continue stirring for 4-6 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 45-60° C. for 4-8 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 1-3 hours, then place it in a vacuum drying oven at 65-80° C. and dry it for 16-24 hours to obtain catalyst B.
[0016] The molar ratio of cerium sulfate to antimony glycol is (1-1.5): (2-3); the loading amount of cerium sulfate accounts for 15%-20% of the mass of silica, the amount of tetrabutyl titanate used is 2-4% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone used is 0.5-1.2% of the total mass of catalyst B; the amount of phosphite used is 0.1-0.3% of the total mass of catalyst B.
[0017] Cerium sulfate has a unique rare earth metal ion active center, which can promote the activation of the carboxyl group of terephthalic acid by forming coordination bonds with the reactant molecules. The antimony ions in ethylene glycol antimony can also interact with the reactants, and they mainly act on the hydroxyl groups of ethylene glycol to enhance the nucleophilicity of the hydroxyl groups. After the two are compounded, the reactants are activated from different angles. Cerium sulfate activates the carboxyl group, and ethylene glycol antimony activates the hydroxyl group. This complementarity of active centers can greatly increase the rate of the polycondensation reaction. Cerium sulfate can accelerate the deprotonation process of the carboxyl group, while ethylene glycol antimony is conducive to the attack of the hydroxyl group of ethylene glycol, so that the reaction can proceed smoothly at a lower temperature and pressure, reducing the occurrence of side reactions. As a supporting material, silica provides a high specific surface area dispersion platform for cerium sulfate. Cerium sulfate is dispersed on the surface and pores of silica, avoiding the agglomeration of the active center, so that the active center of cerium sulfate can be more fully in contact with the reactant. At the same time, the stability of silica can prevent cerium sulfate from sintering or deactivation under reaction conditions such as high temperature, thereby maintaining the activity and stability of catalyst B. The surface of silica has certain adsorption properties, which can adsorb reactant molecules and enrich the reactants near the active center of cerium sulfate. After being adsorbed on the surface of silica, terephthalic acid and ethylene glycol molecules are more likely to react with the active center of cerium sulfate, thereby improving the efficiency of the reaction. Tetrabutyl titanate is used as a co-catalyst, and its titanium atoms can interact with the active centers of cerium sulfate and antimony glycol. The titanium-oxygen bond in tetrabutyl titanate has certain activity, and it can form a transition state complex with the reactant molecules to promote the activation of the reactants. After compounding with cerium sulfate and antimony glycol, this synergistic effect can further reduce the activation energy of the reaction and accelerate the reaction rate. Polyvinyl pyrrolidone forms an interfacial film between cerium sulfate and the reaction medium, which improves the compatibility of cerium sulfate with the reaction system. This makes it easier for the reactant molecules to approach the active center of cerium sulfate, and is also conducive to the timely diffusion of the reaction products, avoiding the accumulation of products on the surface of catalyst B, thereby maintaining the activity of catalyst B. Phosphite can form a weak interaction with the active center of catalyst B, and regulate the activity of catalyst B, so that while ensuring the reaction rate, it reduces side reactions caused by over-catalysis, such as oxidative degradation or thermal degradation reactions, and improves the quality and stability of the product.
[0018] The polyethylene terephthalate is prepared by the above-mentioned method for preparing polyethylene terephthalate.
[0019] The polyethylene terephthalate is used for preparing LED lampshades.
[0020] The preparation of the LED lampshade comprises the following steps: Ⅰ. The obtained polyethylene terephthalate was dried at 135°C-145°C for 3-4h, and then put into a high-speed mixer with hindered phenol antioxidant 1010, phosphite antioxidant 168, light stabilizer, and tributyl citrate, and stirred at 105°C-115°C for 8-10min; then polycarbonate was added and stirring was continued for 3-5min; Ⅱ. Pre-disperse nano-titanium dioxide in polyvinyl pyrrolidone solution, then add it to the mixture obtained in step Ⅰ and stir for 5-8 minutes; III. Add glass fiber, zirconium phosphate and nano talc into the middle glass fiber bucket of the twin-screw extruder, add the organosilicon light diffuser into the extruder through the side feeding device, and melt extrude together with the other materials; IV. The melt after extrusion is cooled and shaped in a cooling water tank, and the cooling water temperature is controlled at 25℃-28℃; the cooled material is passed through an air dryer to remove surface moisture, and then cut into granules by a pelletizer; the cut granules are dried at 85℃-95℃ for 2-3h to remove moisture and residual volatiles; V. The dried particles are made into an LED lampshade through an injection molding process, the injection molding temperature is 265° C.-270° C., the injection molding pressure is 65-70 MPa, and the holding time is 5-8 seconds, thereby obtaining an LED lampshade.
[0021] The amount of the hindered phenol antioxidant 1010 added is 0.2-0.4% of the mass of polyethylene terephthalate, the amount of the phosphite antioxidant 168 added is 0.1-0.3% of the mass of polyethylene terephthalate; the amount of the glass fiber added is 12-15% of the mass of polyethylene terephthalate; the amount of zirconium phosphate added is 2-3% of the mass of polyethylene terephthalate; the amount of nano talc added is 4-6% of the mass of polyethylene terephthalate; the silicone light diffuser The addition amount of is 3-5% of the mass of polyethylene terephthalate; the addition amount of polycarbonate is 25-32% of the mass of polyethylene terephthalate; the addition amount of nano titanium dioxide is 1-2% of the mass of polyethylene terephthalate; the addition amount of tributyl citrate is 4-6% of the mass of polyethylene terephthalate; the addition amount of light stabilizer is 0.2-0.4% of the mass of polyethylene terephthalate; the silicone light diffuser is polydimethylsiloxane; and the light stabilizer is zinc oxide.
[0022] Antioxidant 1010 mainly inhibits the chain initiation and chain growth process of the oxidation reaction by capturing free radicals, while antioxidant 168 can decompose hydroperoxides and prevent the further development of the oxidation reaction. This combination can effectively prevent the oxidative degradation of PET under a wider range of temperature and processing conditions and improve its anti-aging performance. The network structure formed by the glass fiber can limit the movement of the PET molecular chain, and zirconium phosphate can fill the gap between the glass fiber and PET to further enhance the stability of the system. At the same time, zirconium phosphate can also improve the interfacial compatibility between the glass fiber and PET, so that the stress of the material can be more evenly distributed when subjected to external force or high temperature. The tiny particles of nano-talc can act as light scattering centers and cooperate with the silicone light diffuser to make the light more evenly scattered inside the material, thereby achieving a better light diffusion effect while ensuring good light transmittance. The presence of nano-talc can also enhance the structural stability of the material, prevent the agglomeration of the light diffuser, and help maintain the long-term stability of the optical properties of the lampshade. The molecular chains of polycarbonate (PC) can be entangled with the molecular chains of PET to form an interpenetrating network structure. This structure can further enhance the high temperature resistance while improving the toughness of the material. During the processing, since the processing temperature ranges of PC and PET overlap to a certain extent, the two can be fully mixed by controlling the appropriate temperature (250℃-260℃) and screw speed (355-425rpm) during melt blending in a twin-screw extruder. The addition of PC can also improve the solvent resistance of the material, because PC itself has good tolerance to some organic solvents, and synergistically with PET, it can resist the erosion of more types of solvents. The photocatalytic properties of TiO2 can synergize with tributyl citrate to further inhibit the oxidation reaction of the material under light conditions, reduce the glass transition temperature of PET, and improve the flexibility of the material. When used with reinforcing materials such as glass fiber, it can balance the rigidity and toughness of the material to a certain extent. Zirconium phosphate can form a stable carbon layer at high temperature, which can effectively block the transfer of heat and oxygen and prevent the further spread of flames. Phosphite antioxidants 168 and phosphite antioxidants 1010 have a synergistic effect, jointly improving the thermal stability and antioxidant properties of the material, thereby indirectly enhancing the structural stability of the material at high temperatures, and having a certain auxiliary effect on the flame retardant properties. When encountering flames, flaky talcum powder can form a barrier layer on the surface of the material to reduce the transfer of heat and oxygen, and also inhibit the decomposition and combustion of the polymer. Glass fiber can prevent the flow and dripping of the polymer and reduce the spread of flames, thereby significantly improving the flame retardant effect of the material.
[0023] Twin-screw extruder parameters: zone 1 temperature is 173℃-176℃, zone 2 temperature is 246℃-252℃, zone 3 temperature is 248℃-255℃, zone 4 temperature is 252℃-260℃, zone 5 temperature is 250℃-255℃, zone 6 temperature is 226℃-232℃, zone 7 temperature is 224℃-235℃, zone 8 temperature is 220℃-230℃, die head temperature is 245℃-255℃, screw speed is 355-425rpm.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) Catalyst A was prepared by loading p-toluenesulfonic acid and stannous octoate on MCM-41 molecular sieve; MCM-41 molecular sieve has a large specific surface area and a regular pore structure, which can make the active components highly dispersed and increase the exposure of active sites, thereby greatly improving the activity of catalyst A; catalyst B is compounded with cerium sulfate and ethylene glycol antimony as main raw materials, and is prepared through a series of steps such as silica loading to greatly improve the reaction efficiency; by using catalyst A and catalyst B in combination, the conversion rate and production efficiency of polyethylene terephthalate are greatly improved, and the occurrence of side reactions is reduced.
[0025] (2) This method can produce polyethylene terephthalate with a relatively concentrated molecular weight distribution, which has good mechanical properties, such as high tensile strength, flexural strength and impact strength, and can meet the basic requirements for being used as a material for LED lampshades; at the same time, it has good thermal stability, suitable glass transition temperature and melting temperature, is easy to shape during processing, and can withstand the heat generated by LED lamps during use and is not easy to deform.
[0026] (3) The LED lampshade produced by the present invention has good light transmittance and light diffusion performance, and can make the light of the LED lamp pass through the lampshade evenly; at the same time, its high UV resistance can ensure that the optical performance of the lampshade will not be significantly reduced due to ultraviolet radiation during long-term use; by adding various reinforcing materials, its mechanical properties such as tensile strength, bending strength and impact strength are significantly improved, and it can withstand various external forces during transportation, installation and use, and is not easy to be damaged, thereby ensuring the reliability and durability of the product; its good thermal stability enables the shape to remain stable when the LED lamp generates heat during operation, and will not be deformed or damaged due to temperature changes, thereby extending the service life of the lampshade. DETAILED DESCRIPTION
[0027] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.
[0028] Example 1 The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 20 min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.3 mol / L, then add the solution dropwise to the suspension of MCM-41, stir at 23°C for 9 h at a stirring speed of 400 rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.2 mol / L solution, slowly add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 13h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and the reaction was stirred at 70 ° C for 6h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances are detected in the washing liquid, and then dry the filter cake at 100°C for 10 hours to obtain a supported composite catalyst, and then calcine the dried catalyst at 400°C for 5 hours to obtain catalyst A.
[0029] Among them, the loading amount of p-toluenesulfonic acid is 14% of the total mass of catalyst A, the loading amount of stannous octoate is 9% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 3% of the total mass of catalyst A.
[0030] The preparation method of catalyst B comprises the following steps: ① Calcinate silicon dioxide at 580°C for 5 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.5 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 24 hours; ② Dry the impregnated sample at 110℃ for 18h and then calcine at 510℃ for 4h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then drop tetrabutyl titanate into the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 5 hours, then add the ethylene glycol antimony solution to the above system, and continue stirring for 5 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 50° C. for 8 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 2 hours, then place it in a vacuum drying oven at 73° C. and dry it for 20 hours to obtain catalyst B.
[0031] Among them, the molar ratio of cerium sulfate to antimony glycol is 1.5:2; the loading amount of cerium sulfate is 18% of the mass of silica, the amount of tetrabutyl titanate is 3% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone is 1% of the total mass of catalyst B; the amount of phosphite is 0.2% of the total mass of catalyst B.
[0032] The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 230°C and a pressure of 0.2 MPa for 3 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 280°C and a pressure of 2700Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 293°C and a pressure of 270 Pa to further grow the molecular chain and obtain polyethylene terephthalate. The conversion rate of the final polycondensation reaction is calculated to be 97.1%.
[0033] Example 2 The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 25 min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.5 mol / L, then add the solution dropwise to the suspension of MCM-41, stir for 10 h at 25 ° C, and stir at a speed of 480 rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.2 mol / L solution, slowly add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 14h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and the reaction was stirred at 75 ° C for 7h; e. The suspension obtained in step d was filtered, and the filter cake was washed with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances were detected in the washing liquid, and then the filter cake was dried at 110° C. for 10 h to obtain a supported composite catalyst, and then the dried catalyst was calcined at 420° C. for 6 h to obtain catalyst A.
[0034] Among them, the loading amount of p-toluenesulfonic acid is 16% of the total mass of catalyst A, the loading amount of stannous octoate is 10% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 4% of the total mass of catalyst A.
[0035] The preparation method of catalyst B comprises the following steps: ① Calcinate silicon dioxide at 550°C for 4 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.3 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 18 hours; ② Dry the impregnated sample at 100-120℃ for 16h and then calcine at 450℃ for 3h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then drop tetrabutyl titanate into the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 3 hours, then add ethylene glycol antimony solution to the above system, and continue stirring for 4 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 45° C. for 4 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 1 hour, then place it in a vacuum drying oven at 65° C. and dry it for 16 hours to obtain catalyst B.
[0036] Among them, the molar ratio of cerium sulfate to antimony glycol is 1:2; the loading amount of cerium sulfate is 15% of the mass of silica, the amount of tetrabutyl titanate is 2% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone is 0.5% of the total mass of catalyst B; the amount of phosphite is 0.1% of the total mass of catalyst B.
[0037] The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 235°C and a pressure of 0.3 MPa for 3.5 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 284°C and a pressure of 2550Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 295°C and a pressure of 285 Pa to further grow the molecular chain and obtain polyethylene terephthalate. The conversion rate of the final polycondensation reaction is calculated to be 96.7%.
[0038] Example 3 The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 18 minutes to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.1 mol / L, then add the solution dropwise to the suspension of MCM-41, stir at 20°C for 8 h at a stirring speed of 350 rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.1 mol / L solution, slowly add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 12h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and stirred at 65 ° C for 5 h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances are detected in the washing liquid, and then dry the filter cake at 95°C for 9h to obtain a supported composite catalyst, and then calcine the dried catalyst at 385°C for 3h to obtain catalyst A.
[0039] Among them, the loading amount of p-toluenesulfonic acid is 12% of the total mass of the catalyst, the loading amount of stannous octoate is 8% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 2% of the total mass of catalyst A.
[0040] The preparation method of catalyst B comprises the following steps: ① Calcinate silicon dioxide at 600°C for 6 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.8 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 28 hours; ② Dry the impregnated sample at 120℃ for 20h and then calcine at 550℃ for 6h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then drop tetrabutyl titanate into the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 6 hours, then add the ethylene glycol antimony solution to the above system, and continue stirring for 6 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 60° C. for 8 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 3 hours, then place it in a vacuum drying oven at 80° C. and dry it for 24 hours to obtain catalyst B.
[0041] Among them, the molar ratio of cerium sulfate to antimony glycol is 1.5:3; the loading amount of cerium sulfate is 20% of the mass of silica, the amount of tetrabutyl titanate is 4% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone is 1.2% of the total mass of catalyst B; the amount of phosphite is 0.3% of the total mass of catalyst B.
[0042] The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid (PTA) and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 225°C and a pressure of 0.05 MPa for 2.5 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 275°C and a pressure of 2550Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 290°C and a pressure of 255 Pa to further grow the molecular chain and obtain polyethylene terephthalate. The conversion rate of the final polycondensation reaction is calculated to be 96.4%.
[0043] Example 4 The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 20 min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.5 mol / L, then add the solution dropwise to the suspension of MCM-41, stir for 10 h at 25 ° C, and stir at a speed of 480 rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.2 mol / L solution, slowly add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 13h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and the reaction was stirred at 70 ° C for 6h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances are detected in the washing liquid, and then dry the filter cake at 100°C for 10 hours to obtain a supported composite catalyst, and then calcine the dried catalyst at 400°C for 5 hours to obtain catalyst A.
[0044] Among them, the loading amount of p-toluenesulfonic acid is 14% of the total mass of catalyst A, the loading amount of stannous octoate is 9% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 3% of the total mass of catalyst A.
[0045] The preparation method of catalyst B comprises the following steps: ① Calcinate silicon dioxide at 550°C for 4 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.3 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 18 hours; ② Dry the impregnated sample at 100-120℃ for 16h and then calcine at 450℃ for 3h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then add tetrabutyl titanate dropwise to the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 3 hours, then add ethylene glycol antimony solution to the above system, and continue stirring for 6 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 50° C. for 8 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 1 hour, then place it in a vacuum drying oven at 65° C. and dry it for 16 hours to obtain catalyst B.
[0046] Among them, the molar ratio of cerium sulfate to antimony glycol is 1:2; the loading amount of cerium sulfate is 15% of the mass of silica, the amount of tetrabutyl titanate is 2% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone is 0.5% of the total mass of catalyst B; the amount of phosphite is 0.1% of the total mass of catalyst B.
[0047] The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 235°C and a pressure of 0.3 MPa for 3.5 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 284°C and a pressure of 2550Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 295°C and a pressure of 285 Pa to further grow the molecular chain and obtain polyethylene terephthalate. The conversion rate of the final polycondensation reaction is calculated to be 96.2%.
[0048] Example 5 The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 18 minutes to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.1 mol / L, then add the solution dropwise to the suspension of MCM-41, stir at 20°C for 8 h at a stirring speed of 350 rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.2 mol / L solution, slowly add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 14h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and stirred at 65 ° C for 5 h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances are detected in the washing liquid, and then dry the filter cake at 95°C for 9h to obtain a supported composite catalyst, and then calcine the dried catalyst at 385°C for 3h to obtain catalyst A.
[0049] Among them, the loading amount of p-toluenesulfonic acid is 12% of the total mass of catalyst A, the loading amount of stannous octoate is 8% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 2% of the total mass of catalyst A.
[0050] The preparation method of catalyst B comprises the following steps: ① Calcinate silicon dioxide at 580°C for 5 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.5 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 24 hours; ② Dry the impregnated sample at 110℃ for 18h and then calcine at 510℃ for 4h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then drop tetrabutyl titanate into the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 5 hours, then add ethylene glycol antimony solution to the above system, and continue stirring for 4 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 45° C. for 4 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 2 hours, then place it in a vacuum drying oven at 73° C. and dry it for 20 hours to obtain catalyst B.
[0051] Among them, the molar ratio of cerium sulfate to antimony glycol is 1.5:2; the loading amount of cerium sulfate is 18% of the mass of silica, the amount of tetrabutyl titanate is 3% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone is 1% of the total mass of catalyst B; the amount of phosphite is 0.2% of the total mass of catalyst B.
[0052] The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 230°C and a pressure of 0.2 MPa for 3 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 280°C and a pressure of 2700Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 293°C and a pressure of 270 Pa to further grow the molecular chain and obtain polyethylene terephthalate. The conversion rate of the final polycondensation reaction is calculated to be 96.1%.
[0053] Comparative Example 1 Compared with Example 1, the difference is: The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 20 min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Stannous octoate was dissolved in toluene to prepare a 0.2 mol / L solution, and the stannous octoate solution was slowly added dropwise to the suspension in step a under stirring, and stirring was continued for 13h to load stannous octoate onto MCM-41; in this process, nitrogen protection was used; c. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with stannous octoate in step c, and stirred at 70 ° C for 6 h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol until no free stannous octoate and other substances are detected in the washing liquid, and then dry the filter cake at 100°C for 10 hours to obtain a supported composite catalyst, and then calcine the dried catalyst at 400°C for 5 hours to obtain catalyst A.
[0054] The loading amount of stannous octoate is 9% of the total mass of catalyst A, and the addition amount of triphenyl phosphate is 3% of the total mass of catalyst A. After calculation, the conversion rate of the final polycondensation reaction is 91.1%.
[0055] Comparative Example 2 Compared with Example 2, the difference is: The preparation method of catalyst A comprises the following steps: a. The calcined MCM-41 molecular sieve was added to ethanol and ultrasonically dispersed for 25 min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.5 mol / L, then add the solution dropwise to the suspension of MCM-41, stir for 10 h at 25 ° C, and stir at a speed of 480 rpm; c. Boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1 and dissolved in toluene to form a mixed solution, which was added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and stirred at 75 ° C for 7h; e. The suspension obtained in step d was filtered, and the filter cake was washed with a mixture of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances were detected in the washing liquid, and then the filter cake was dried at 110° C. for 10 h to obtain a supported composite catalyst, and then the dried catalyst was calcined at 420° C. for 6 h to obtain catalyst A.
[0056] The loading amount of p-toluenesulfonic acid is 18% of the total mass of catalyst A, and the loading amount of stannous octoate is 10% of the total mass of catalyst A. According to calculation, the conversion rate of the final polycondensation reaction is 90.3%.
[0057] Comparative Example 3 Compared with Example 1, the difference is: The preparation method of catalyst A comprises the following steps: a. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.3 mol / L, stir at 23°C for 9 h at a stirring speed of 400 rpm; b. Take stannous octoate and dissolve it in toluene to prepare a 0.2 mol / L solution, the p-toluenesulfonic acid solution in step a, slowly add the stannous octoate solution dropwise under stirring, and continue stirring for 13h. During this process, nitrogen protection is used; c. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1 and dissolved in toluene to form a mixed solution, which was added to the solution obtained in step c and stirred at 70 ° C for 6 h; d. Filter the mixed solution obtained in step c, wash the filter cake with a mixed solution of toluene and ethanol until no free p-toluenesulfonic acid, stannous octoate and other substances are detected in the washing solution, and then dry the filter cake at 100°C for 10 hours to obtain a composite catalyst, and then calcine the dried catalyst at 400°C for 5 hours to obtain catalyst A.
[0058] The added amounts of p-toluenesulfonic acid, stannous octoate and triphenyl phosphate are the same as those in Example 1.
[0059] The preparation method of polyethylene terephthalate comprises the following steps: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 230°C and a pressure of 0.2 MPa for 3 hours to generate ethylene terephthalate oligomers. (2) Polycondensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction was transported to a polycondensation reactor, ethylene glycol and catalyst B were added, and a polycondensation reaction was carried out at a temperature of 293°C and a pressure of 270 Pa to further grow the molecular chain and obtain polyethylene terephthalate. The conversion rate of the final polycondensation reaction was calculated to be 91.2%.
[0060] Comparative Example 4 Compared with Example 3, the difference is: The preparation method of catalyst B comprises the following steps: ① Calcine silicon dioxide at 600°C for 6 hours; ② Dissolve tetrabutyl titanate in ethanol, add the calcined silicon dioxide in step ① to the ethanol solution of tetrabutyl titanate, stir at room temperature for 12 hours, then add the ethylene glycol antimony solution to the above system, and continue stirring for 6 hours; ③ Add the phosphite to the catalyst system obtained in step ②, stir at room temperature for 3 hours, then place it in a vacuum drying oven at 80° C. and dry it for 24 hours to obtain catalyst B.
[0061] The mass ratio of antimony glycolate to silicon dioxide is 2:3.35, the amount of tetrabutyl titanate is 2.68% of the mass of antimony glycolate, the amount of polyvinyl pyrrolidone is 1.2% of the total mass of catalyst B, and the amount of phosphite is 0.3% of the total mass of catalyst B. After calculation, the conversion rate of the final polycondensation reaction is 87.6%.
[0062] Comparative Example 5 Compared with Example 1, the difference is: The preparation method of catalyst B comprises the following steps: ① Calcinate silicon dioxide at 580°C for 5 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.5 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 24 hours; ② Dry the impregnated sample at 110℃ for 18h and then calcine at 510℃ for 4h; ③ Dissolve tetrabutyl titanate in ethanol, then add tetrabutyl titanate dropwise to the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, and stir at room temperature for 5 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add the solution to the catalyst system containing tetrabutyl titanate obtained in step ③, and stir at 50° C. for 8 hours; ⑤ Place the catalyst system obtained in step ④ in a vacuum drying oven and dry at 73°C for 20 hours to obtain catalyst B.
[0063] Among them, the loading amount of cerium sulfate accounts for 26% of the mass of silica, the amount of tetrabutyl titanate is 3% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone is 1% of the total mass of catalyst B; the amount of phosphite is 0.2% of the total mass of catalyst B. According to calculation, the conversion rate of the final polycondensation reaction is 88.2%.
[0064] The test data of catalyst A obtained in Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.
[0065] The test data of catalyst B obtained in Examples 1-5 and Comparative Examples 4-5 are shown in Table 2.
[0066] The test data of the polyethylene terephthalate obtained in Examples 1-5 and Comparative Examples 1-5 are shown in Table 3.
[0067] Table 1 Test data of catalyst A obtained from Examples 1-5 and Comparative Examples 1-3
[0068] It can be seen from Table 1 that when the active components in Catalyst A are used alone, their catalytic activity is significantly reduced when used in combination, and the load has a huge impact on the performance of Catalyst A. The acidic active center of p-toluenesulfonic acid activates the reactants mainly through protonation, while the metal active center of stannous octoate changes the electron cloud distribution of the reactants through coordination, thereby improving its reaction activity. The active centers of the two are complementary, and after compounding, the reactants can be activated from different angles, thereby improving the overall catalytic efficiency of Catalyst A.
[0069] Table 2 Test data of catalyst B obtained from Examples 1-5 and Comparative Examples 4-5
[0070] Note: “Catalytic activity / ×10 4 In "gM / gcat", M is an ethylene terephthalate oligomer.
[0071] As shown in Table 2, the compounding of ethylene glycol antimony and ethylene glycol antimony greatly improves the activity of catalyst B. After the two are compounded, the reactants are activated from different angles. Cerium sulfate activates the carboxyl group and ethylene glycol antimony activates the hydroxyl group. The complementarity of the active centers can greatly increase the rate of the polycondensation reaction. Cerium sulfate can accelerate the deprotonation process of the carboxyl group, while ethylene glycol antimony is conducive to the attack of the ethylene glycol hydroxyl group, so that the reaction can proceed smoothly at a lower temperature and pressure, reducing the occurrence of side reactions.
[0072] Table 3 Test data of polyethylene terephthalate obtained from Examples 1-5 and Comparative Examples 1-5
[0073] It can be seen from Table 3 that the polyethylene terephthalate prepared in the embodiment has a concentrated molecular weight distribution, high mechanical strength and excellent optical properties. On the contrary, the product prepared in the comparative example shows a decrease in overall performance after the catalyst is changed and the esterification and polycondensation reaction conditions are adjusted, which is quite different from the embodiment.
[0074] Application Example 1 The preparation of the LED lampshade comprises the following steps: Ⅰ. The polyethylene terephthalate obtained in Example 1 was dried at 140°C for 4h, and then placed in a high-speed mixer with hindered phenol antioxidant 1010, phosphite antioxidant 168, light stabilizer, and tributyl citrate, and stirred at 110°C for 9min; then polycarbonate was added and stirring was continued for 4min; Ⅱ. Pre-disperse nano-titanium dioxide in polyvinyl pyrrolidone solution, add it to the mixture obtained in step Ⅰ, and stir for 7 minutes; III. Add glass fiber, zirconium phosphate and nano talc into the middle glass fiber bucket of the twin-screw extruder, add the organosilicon light diffuser into the extruder through the side feeding device, and melt extrude together with the other materials; IV. The melt after extrusion is cooled and shaped in a cooling water tank, and the cooling water temperature is controlled at 27°C; the cooled material is passed through an air dryer to remove surface moisture, and then cut into granules by a pelletizer; the cut granules are dried at 90°C for 3 hours to remove moisture and residual volatiles; V. The dried particles were made into an LED lampshade through an injection molding process, with an injection molding temperature of 268° C., an injection molding pressure of 68 MPa, and a holding time of 6 seconds to obtain an LED lampshade.
[0075] Among them, the addition amount of hindered phenol antioxidant 1010 is 0.3% of the mass of polyethylene terephthalate, the addition amount of phosphite antioxidant 168 is 0.2% of the mass of polyethylene terephthalate; the addition amount of glass fiber is 13% of the mass of polyethylene terephthalate; the addition amount of zirconium phosphate is 3% of the mass of polyethylene terephthalate; the addition amount of nano talc is 5% of the mass of polyethylene terephthalate; the addition amount of silicone light diffuser is 10%. The added amount is 4% of the mass of polyethylene terephthalate; the added amount of polycarbonate is 30% of the mass of polyethylene terephthalate; the added amount of nano titanium dioxide is 2% of the mass of polyethylene terephthalate; the added amount of tributyl citrate is 5% of the mass of polyethylene terephthalate; the added amount of light stabilizer is 0.3% of the mass of polyethylene terephthalate; the silicone light diffuser is polydimethylsiloxane; and the light stabilizer is zinc oxide.
[0076] Twin-screw extruder parameters: zone 1 temperature is 175°C, zone 2 temperature is 250°C, zone 3 temperature is 252°C, zone 4 temperature is 255°C, zone 5 temperature is 255°C, zone 6 temperature is 230°C, zone 7 temperature is 228°C, zone 8 temperature is 225°C, die head temperature is 250°C, screw speed is 400rpm.
[0077] Application Example 2 The preparation of the LED lampshade comprises the following steps: Ⅰ. The polyethylene terephthalate obtained in Example 1 was dried at 145°C for 4h, and then placed in a high-speed mixer with hindered phenol antioxidant 1010, phosphite antioxidant 168, light stabilizer, and tributyl citrate, and stirred at 115°C for 10min; then polycarbonate was added and stirring was continued for 5min; Ⅱ. Pre-disperse nano-titanium dioxide in polyvinyl pyrrolidone solution, add it to the mixture obtained in step Ⅰ, and stir for 8 minutes; III. Add glass fiber, zirconium phosphate and nano talc into the middle glass fiber bucket of the twin-screw extruder, add the organosilicon light diffuser into the extruder through the side feeding device, and melt extrude together with the other materials; IV. The melt after extrusion is cooled and shaped in a cooling water tank, and the cooling water temperature is controlled at 28°C; the cooled material is passed through an air dryer to remove surface moisture, and then cut into granules by a pelletizer; the cut granules are dried at 95°C for 3 hours to remove moisture and residual volatiles; V. The dried particles were made into an LED lampshade through an injection molding process, with an injection molding temperature of 270° C., an injection molding pressure of 70 MPa, and a holding time of 8 seconds to obtain an LED lampshade.
[0078] Among them, the addition amount of hindered phenol antioxidant 1010 is 0.4% of the mass of polyethylene terephthalate, the addition amount of phosphite antioxidant 168 is 0.3% of the mass of polyethylene terephthalate; the addition amount of glass fiber is 15% of the mass of polyethylene terephthalate; the addition amount of zirconium phosphate is 3% of the mass of polyethylene terephthalate; the addition amount of nano talc is 6% of the mass of polyethylene terephthalate; the addition amount of silicone light diffuser is 10%. The added amount is 5% of the mass of polyethylene terephthalate; the added amount of polycarbonate is 32% of the mass of polyethylene terephthalate; the added amount of nano titanium dioxide is 2% of the mass of polyethylene terephthalate; the added amount of tributyl citrate is 6% of the mass of polyethylene terephthalate; the added amount of light stabilizer is 0.4% of the mass of polyethylene terephthalate; the silicone light diffuser is polydimethylsiloxane; and the light stabilizer is zinc oxide.
[0079] Twin-screw extruder parameters: zone 1 temperature is 173°C, zone 2 temperature is 246°C, zone 3 temperature is 248°C, zone 4 temperature is 252°C, zone 5 temperature is 250°C, zone 6 temperature is 226°C, zone 7 temperature is 224°C, zone 8 temperature is 220°C, die head temperature is 245°C, and screw speed is 355rpm.
[0080] Application Example 3 The preparation of the LED lampshade comprises the following steps: Ⅰ. The polyethylene terephthalate obtained in Example 2 was dried at 135°C for 3h, and then placed in a high-speed mixer with hindered phenol antioxidant 1010, phosphite antioxidant 168, light stabilizer, and tributyl citrate, and stirred at 105°C for 8min; then polycarbonate was added and stirring was continued for 3min; Ⅱ. Pre-disperse the nano-titanium dioxide in the polyvinyl pyrrolidone solution, then add it to the mixture obtained in step Ⅰ and stir for 5 minutes; III. Add glass fiber, zirconium phosphate and nano talc into the middle glass fiber bucket of the twin-screw extruder, add the organosilicon light diffuser into the extruder through the side feeding device, and melt extrude together with the other materials; IV. The melt after extrusion is cooled and shaped in a cooling water tank, and the cooling water temperature is controlled at 25°C; the cooled material is passed through an air dryer to remove surface moisture, and then cut into granules by a pelletizer; the cut granules are dried at 85°C for 2h to remove moisture and residual volatiles; V. The dried particles were made into an LED lampshade through an injection molding process, with an injection molding temperature of 265° C., an injection molding pressure of 65 MPa, and a holding time of 5 seconds to obtain an LED lampshade.
[0081] Among them, the addition amount of hindered phenol antioxidant 1010 is 0.2% of the mass of polyethylene terephthalate, the addition amount of phosphite antioxidant 168 is 0.1% of the mass of polyethylene terephthalate; the addition amount of glass fiber is 12% of the mass of polyethylene terephthalate; the addition amount of zirconium phosphate is 2% of the mass of polyethylene terephthalate; the addition amount of nano talc is 4% of the mass of polyethylene terephthalate; the addition amount of silicone light diffuser is 1.2%. The added amount is 3% of the mass of polyethylene terephthalate; the added amount of polycarbonate is 25% of the mass of polyethylene terephthalate; the added amount of nano titanium dioxide is 1% of the mass of polyethylene terephthalate; the added amount of tributyl citrate is 4% of the mass of polyethylene terephthalate; the added amount of light stabilizer is 0.2% of the mass of polyethylene terephthalate; the silicone light diffuser is polydimethylsiloxane; and the light stabilizer is zinc oxide.
[0082] Twin-screw extruder parameters: zone 1 temperature is 176°C, zone 2 temperature is 252°C, zone 3 temperature is 255°C, zone 4 temperature is 260°C, zone 5 temperature is 255°C, zone 6 temperature is 232°C, zone 7 temperature is 235°C, zone 8 temperature is 230°C, die head temperature is 255°C, and screw speed is 425rpm.
[0083] Application Comparative Example 1 Compared with Application Example 1, the difference is that the antioxidant 1010 and the glass fiber are not added.
[0084] Application Comparative Example 2 Compared with Application Example 1, the difference is that the antioxidant 168, zirconium phosphate and polycarbonate are not added.
[0085] Application Comparative Example 3 Compared with Application Example 2, the difference is that no nano talc powder and TiO2 are added; the parameters of the twin-screw extruder are: the temperature of zone 1 is 170°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 240°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 220°C, the temperature of zone 7 is 215°C, the temperature of zone 8 is 215°C, the die head temperature is 240°C, and the screw speed is 320rpm.
[0086] The test data of application examples 1-3 and application comparative examples 1-3 are shown in Table 4.
[0087] Test method: UV resistance test: Select UVA-340 lamps with a specific wavelength to irradiate the LED lampshade samples. Place the samples in a UV lamp aging test chamber, set the light intensity to 0.5-1.0W / m² / nm, the temperature to 30℃-50℃, and the test time to 300 hours. After the test, check the appearance changes of the samples, including color fading, surface cracking, deformation, etc., to determine the material's anti-ultraviolet aging performance.
[0088] Chemical corrosion resistance test: According to GB / T10125, the LED lampshade samples are placed in a salt spray test chamber, and sodium chloride solution is used to simulate seawater or salt spray environment. The solution concentration is 5%±1% and the pH value is between 6.5-7.2. The test temperature is set at 35℃±2℃, the spray pressure is 70kPa-170kPa, and the spray time is 500 hours. After the test, take out the sample, rinse it with clean water, and observe whether there are corrosion spots, bubbling, peeling, etc. on the surface of the sample to evaluate its salt spray corrosion resistance.
[0089] Flame retardant grade test: According to GB / T2408 standard, prepare LED lampshade samples of specified size, place the samples horizontally on the fixture of the horizontal combustion test machine, ignite one end of the sample with a Bunsen burner, adjust the flame height to 20mm±2mm, and the ignition time is 30 seconds. Observe the spread of the flame on the sample, record the position and time of the flame front arrival, and calculate the burning speed. At the same time, observe whether the sample has molten droplets and whether the molten droplets ignite the absorbent cotton. According to the test results, evaluate its flame retardant grade against the corresponding standards.
[0090] The standards for evaluating flame retardancy are as follows: HB grade: When the sample thickness is less than 3mm, the burning speed is less than 76mm / min; when the sample thickness is equal to 3mm, the burning speed is less than 40mm / min; or within a span of 100mm, the time for the flame front to stop burning does not exceed 40s.
[0091] V-0: After each application of flame to a single sample, the flame shall not last for more than 10 seconds, and after 10 applications of flame to each group of 5 samples, the total flame shall not last for more than 50 seconds. After each application of flame, the sample shall extinguish itself within 30 seconds, and no burning material shall fall off.
[0092] V-1: After each application of flame to a single sample, the flame shall not last for more than 30 seconds, and after 10 applications of flame to each group of 5 samples, the total flame shall not last for more than 250 seconds. After each application of flame, the sample shall self-extinguish within 60 seconds, and no burning material shall fall and ignite absorbent cotton, etc.
[0093] V-2: After each application of flame to a single sample, the flame continues to burn for no more than 30 seconds, and after 10 applications of flame to each group of 5 samples, the total flame burning time does not exceed 250 seconds. Burning objects are allowed to fall, but they cannot ignite absorbent cotton, etc.
[0094] Table 4 Test data of application examples 1-3 and application comparative examples 1-3
[0095] It can be seen from the data in Table 4 that the LED lampshade prepared by applying the embodiment has excellent optical properties, good mechanical properties, high flame retardant grade, and strong chemical corrosion resistance and UV resistance; while the LED lampshade prepared by applying the comparative example has significantly reduced UV resistance, flame retardant grade and optical properties.
Claims
1. A method for preparing polyethylene terephthalate, characterized in that: The following steps are involved: (1) Esterification reaction: Add terephthalic acid and ethylene glycol into an esterification kettle, start stirring, and add catalyst A at the same time. Perform esterification reaction at a temperature of 225-235°C and a pressure of 0.05-0.3 MPa for 2.5-3.5 hours to generate ethylene terephthalate oligomers. (2) Pre-condensation reaction: The ethylene terephthalate oligomer obtained by the esterification reaction is transported to a pre-condensation reactor, ethylene glycol and catalyst B are added, and a pre-condensation reaction is carried out at a temperature of 275-284°C and a pressure of 2550-2800Pa; a vacuum system is provided on the pre-condensation reactor; (3) Final polycondensation reaction: The product obtained from the preliminary polycondensation reaction enters the final polycondensation reactor and undergoes a polycondensation reaction at a temperature of 290-295°C and a pressure of 255-285Pa to obtain polyethylene terephthalate; The catalyst A is a composite catalyst loaded on MCM-41 with p-toluenesulfonic acid and stannous octoate as raw materials, and the catalyst B is a composite catalyst with cerium sulfate and antimony ethylene glycol as raw materials; In the step (1), the mass ratio of ethylene glycol to terephthalic acid is (1.08-1.12):
1.
2. The method for preparing polyethylene terephthalate according to claim 1, characterized in that: In the step (1), the amount of catalyst A added is 0.05-0.1% of the total mass of the reactants in the esterification reaction; in the step (2), the amount of ethylene glycol added is 2.2-4% of the mass of ethylene terephthalate oligomers, and the amount of catalyst B added is 0.02-0.04% of the mass of ethylene terephthalate oligomers.
3. The method for preparing polyethylene terephthalate according to claim 1, characterized in that: In the step (1), the preparation method of catalyst A comprises the following steps: a. Add the calcined MCM-41 molecular sieve to ethanol and ultrasonically disperse it for 18-25min to uniformly disperse the molecular sieve in the solvent to form a suspension; b. Dissolve p-toluenesulfonic acid in ethanol to prepare a solution with a concentration of 0.1-0.5 mol / L, then add the solution dropwise to the suspension of MCM-41, stir at 20-25°C for 8-10h, and stir at a speed of 350-480rpm; c. Take stannous octoate and dissolve it in toluene to prepare a 0.1-0.2 mol / L solution, add the stannous octoate solution dropwise to the suspension of MCM-41 loaded with p-toluenesulfonic acid in step b under stirring, and continue stirring for 12-14h to load stannous octoate onto MCM-41; in this process, nitrogen protection is used; d. triphenyl phosphate, boric acid and tetrabutylammonium bromide were mixed in a molar ratio of 1:1:1, dissolved in toluene to form a mixed solution, added to the MCM-41 suspension loaded with p-toluenesulfonic acid and stannous octoate in step c, and stirred at 65-75 ° C for 5-7h; e. Filter the suspension obtained in step d, wash the filter cake with a mixture of toluene and ethanol, and then dry the filter cake at 95-110°C for 9-10h to obtain a supported composite catalyst, and then calcine the dried catalyst at 385-420°C for 3-6h to obtain catalyst A.
4. The method for preparing polyethylene terephthalate according to claim 3, characterized in that: The loading amount of p-toluenesulfonic acid is 12-16% of the total mass of catalyst A, the loading amount of stannous octoate is 8-10% of the total mass of catalyst A, and the added amount of triphenyl phosphate is 2-4% of the total mass of catalyst A.
5. The method for preparing polyethylene terephthalate according to claim 1, characterized in that: In the step (2), the preparation method of catalyst B comprises the following steps: ① Calcine the silicon dioxide at 550-600°C for 4-6 hours; dissolve cerium sulfate in a dilute nitric acid solution to prepare a solution with a concentration of 0.3-0.8 mol / L; add the treated silicon dioxide to the cerium sulfate solution and immerse it at room temperature for 18-28 hours; ② Dry the impregnated sample at 100-120°C for 16-20h, and then calcine at 450-550°C for 3-6h; ③ Dissolve tetrabutyl titanate in ethanol, dissolve ethylene glycol antimony in ethylene glycol, then drop tetrabutyl titanate into the cerium sulfate-silicon dioxide supported catalyst obtained in step ②, stir at room temperature for 3-6 hours, then add the ethylene glycol antimony solution to the above system, and continue stirring for 4-6 hours; ④ Dissolve polyvinyl pyrrolidone in deionized water to prepare a solution, then add it to the catalyst system obtained in step ③, and stir at 45-60° C. for 4-8 hours; ⑤ Add the phosphite to the catalyst system obtained in step ④, stir at room temperature for 1-3 hours, then place it in a vacuum drying oven at 65-80° C. and dry it for 16-24 hours to obtain catalyst B.
6. The method for preparing polyethylene terephthalate according to claim 5, characterized in that: The molar ratio of cerium sulfate to antimony glycol is (1-1.5): (2-3); the loading amount of cerium sulfate accounts for 15%-20% of the mass of silica, the amount of tetrabutyl titanate used is 2-4% of the mass of cerium sulfate, the amount of polyvinyl pyrrolidone used is 0.5-1.2% of the total mass of catalyst B; the amount of phosphite used is 0.1-0.3% of the total mass of catalyst B.
7. A polyethylene terephthalate, characterized in that: The polyethylene terephthalate is prepared by the preparation method of the polyethylene terephthalate according to any one of claims 1 to 6.
8. An application of the polyethylene terephthalate according to claim 7, characterized in that: Used to prepare LED lampshades.
9. The use of polyethylene terephthalate according to claim 8, characterized in that: The preparation of the LED lampshade comprises the following steps: Ⅰ. The obtained polyethylene terephthalate was dried at 135°C-145°C for 3-4h, and then put into a high-speed mixer with hindered phenol antioxidant 1010, phosphite antioxidant 168, light stabilizer, and tributyl citrate, and stirred at 105°C-115°C for 8-10min; then polycarbonate was added and stirring was continued for 3-5min; Ⅱ. Pre-disperse nano-titanium dioxide in polyvinyl pyrrolidone solution, then add it to the mixture obtained in step Ⅰ and stir for 5-8 minutes; III. Add glass fiber, zirconium phosphate and nano talc into the middle glass fiber bucket of the twin-screw extruder, add the organosilicon light diffuser into the extruder through the side feeding device, and melt extrude together with the other materials; IV. The melt after extrusion is cooled and shaped in a cooling water tank, and the cooling water temperature is controlled at 25℃-28℃; the cooled material is passed through an air dryer to remove surface moisture, and then cut into granules by a pelletizer; the cut granules are dried at 85℃-95℃ for 2-3h to remove moisture and residual volatiles; V. The dried particles are made into an LED lampshade through an injection molding process, the injection molding temperature is 265° C.-270° C., the injection molding pressure is 65-70 MPa, and the holding time is 5-8 seconds, thereby obtaining an LED lampshade.
10. The use of polyethylene terephthalate according to claim 9, characterized in that: The amount of the hindered phenol antioxidant 1010 added is 0.2-0.4% of the mass of polyethylene terephthalate, the amount of the phosphite antioxidant 168 added is 0.1-0.3% of the mass of polyethylene terephthalate; the amount of the glass fiber added is 12-15% of the mass of polyethylene terephthalate; the amount of zirconium phosphate added is 2-3% of the mass of polyethylene terephthalate; the amount of nano talc added is 4-6% of the mass of polyethylene terephthalate; the silicone light diffuser The addition amount of is 3-5% of the mass of polyethylene terephthalate; the addition amount of polycarbonate is 25-32% of the mass of polyethylene terephthalate; the addition amount of nano titanium dioxide is 1-2% of the mass of polyethylene terephthalate; the addition amount of tributyl citrate is 4-6% of the mass of polyethylene terephthalate; the addition amount of light stabilizer is 0.2-0.4% of the mass of polyethylene terephthalate; the silicone light diffuser is polydimethylsiloxane; and the light stabilizer is zinc oxide.
Citation Information
Patent Citations
Method for utilizing molecular sieve supported catalyst to prepare acetic ether
CN105753691A
Supported metal oxide catalyst for catalytically degrading polyethylene glycol terephthalate and preparation method and use thereof
CN109289900A
Supported esterification catalyst, preparation method thereof and application of supported esterification catalyst in methyl methacrylate synthesis reaction
CN116832851A